Determinants of Financial Performance of Commercial Banks: Evidence from Indonesia - Oktapiani, Putu Indah (Journal of Business, Management, and Social Studies, 2022)
The purpose of the study was to examine the determinants of banks’ profitability at commercial banks listed on the Indonesia Stock Exchange. This study employs a quantitative approach that emphasizes objective measurements. The Return on Assets is the dependent variable in this research. In addition, there are four independent variables, namely Loan to Deposit Ratio, Non-Performing Loan, Cost to Income ratio, and Bank Size. The data on Return on Assets was retrieved from Otoritas Jasa Keuangan. In addition, the LDR, NPL, CIR, and Bank Size were also obtained from the bank annual report and Otoritas Jasa Keuangan. The number of samples used in this study was 115 data retrieved from 23 commercial banks during five years of cross-time data. The test results show that Cost to Income ratio and Bank size significantly influence ROA negatively, while Loan to Deposit ratio and Non-Performing loans insignificantly influence ROA. The suggested study will contribute to the growing body of Return on Assets knowledge in the context of commercial banks in Indonesia.